Upregulated hypoxia inducible factor 1α signaling pathway in high risk myelodysplastic syndrome and acute myeloid leukemia patients is associated with better response to 5‐azacytidine—data from the Hellenic myelodysplastic syndrome study group. Issue 2 (1st January 2021) - Mpakou, Vassiliki; Spathis, Aris; Bouchla, Anthi; Tsakiraki, Zoi; Kontsioti, Frieda; Papageorgiou, Sotirios; Bazani, Efthymia; Gkontopoulos, Konstantinos; Thomopoulos, Thomas; Glezou, Irene; Galanopoulos, Athanasios; Symeonidis, Argiris; et al.
Abstract: 5‐azacytidine (5‐AZA) is considered the standard of care for patients with high‐risk myelodysplastic syndromes (MDS) and patients with acute myeloid leukemia (AML) not candidate for intensive chemotherapy. However, even after an initial favorable response, almost all patients relapse, with the exact mechanisms underlying primary or secondary 5‐AZA resistance remaining largely unknown. Several reports have previously demonstrated the significance of hypoxia in the regulation of both physiological and malignant hematopoiesis. In MDS, high hypoxia inducible factor 1α (Hif‐1α) expression has been correlated with poor overall survival and disease progression, while its involvement in the disease's pathogenesis was recently reported. We herein investigated the possible association of the Hif‐1α signaling pathway with response to 5‐AZA therapy in MDS/AML patients. Our data demonstrated that 5‐AZA‐responders present with higher Hif‐1α mRNA and protein expression compared to 5‐AZA‐non‐responders/stable disease patients, before the initiation of therapy, while, interestingly, no significant differences in Hif‐1α mRNA expression at the 6‐month follow‐up were observed. Moreover, we found that 5‐AZA‐responders exhibited elevated mRNA levels of the Hif‐1α downstream targets lactate dehydrogenase a (LDHa) and BCL2 interacting protein 3 like (BNIP3L), a further indication of an overactivated Hif‐1a signaling pathway in these patients. Kaplan–Meier survival analysis revealed a significant correlation between high Hif‐1α mRNA expression and better survival rates, while logistic regression analysis showed that Hif‐1α mRNA expression is an independent predictor of response to 5‐AZA therapy. From the clinical point of view, apart from proposing Hif‐1α mRNA expression as a significant predictive factor for response to 5‐AZA, our data offer new perspectives on MDS combinational therapies, suggesting a potential synergistic activity of 5‐AZA and Hif‐1α inducers, such as propyl hydroxylases inhibitors (PHDi).